Performing euphoric cosmopolitanism: The aesthetics of life and public space in psytrance phantasmagoria. Issue 1 (1st April 2019) - Kyriakopoulos, Leandros
How can we conceive the cosmopolitan ideal of travelling and experiencing exotic difference, so much embraced by 'countercultural' practices, once it is aestheticized into phantasmagorical dream-worlds? How can we think of people getting wasted due to drug-fuelled, long-lasting dancing without resorting to idealisms of 'alternate experiences' and romanticisms about ideal ways of belonging? This article explores psytrance festivals ‐ a cultural product of the Electronic Dance Music (EDM) carnivalesque celebrations, drug consumption (for the most part LSD and MDMA) and euphoric travelling of the 1960s ‐ with an emphasis on cosmopolitanism, aesthetic intimacy and the care of the self. By examining the mobility of Greek aficionados in EDM festivals in Europe, which have gained great popularity since the first decade of the twenty-first century, I discuss the enactment of the chemical celebration in accordance with the sensorial formations, desiring-images and narratives that weave the imagination of psytrance music culture. In contrast with most of the academic literature that views EDM events as a 'heterotopic' set-up that facilitates 'liminal experiences' ‐ supposedly evidence of the possibility of an out-of-the-ordinary lifestyle as opposed to everyday normativity ‐ I propose to investigate the excesses of consumption and bodily expenditure within metaphors that support psytrance technoaesthetics.